Rare consequence of pituitary apoplexy surgery: Artery of percheron infarction - Konar, Subhas; Nishanth, Sadashiva; Devi, B (Asian Journal of Neurosurgery, 2021)
Management of pituitary apoplexy is multimodal. The surgical intervention followed by endocrinological management is the standard of care. Various vascular complications have been described in the literature after pituitary adenoma surgery. Artery of Percheron (AOP) infract is a rare finding. Few cases were reported in the English literature after the endoscopic approach for pituitary adenoma. We present a 55-year-old lady presented with sudden-onset headache followed by vision loss. She was evaluated with imaging and diagnosed pituitary adenoma with apoplexy. She underwent an endoscopic transnasal approach and decompression of the tumor. In the postoperative period, she developed bilateral ptosis with altered sensorium. Imaging showed infarction of bilateral paramedian thalamus and rostral midbrain, suggestive of AOP infarct. Gradually, the patient improved, and at 3 months of follow-up, she was conscious and obeying with partial improvement of ptosis.
Keywords: Artery of Percheron; endoscopic surgery; infarction; pituitary apoplexy